A cross‐sectional study of COVID‐19 pandemic‐related organizational aspects in health care. Issue 2 (16th December 2021) - Jensen, Hanne Irene; Thude, Bettina Ravnborg; Boye, Lilian Keene; Gram, Bibi Valgerdur; Primdahl, Jette; Elkjær, Mette; Specht, Kirsten
Abstract: Aim: This study explores how healthcare professionals included in the COVID‐19 contingency plan experienced organizational changes, and explores factors associated with the experiences. Additionally, the study aimed to identify learning points for future similar scenarios. Design: A cross‐sectional study. Methods: A questionnaire survey of healthcare professionals at three Danish hospitals, June 2020. Results: A total of 1, 448 healthcare professionals completed the questionnaire. Hereof, 813 (57%) were relocated to new settings/new jobs. The majority experienced that their relocation was totally (49%) or partially (31%) imposed, and 51% reported that the overall experience of the new job function was satisfactory. Type of profession and whether relocation to the new job function was imposed were the main variables associated with the overall experience of being part of the contingency plan. Suggestions for future scenarios included training adjusted to individual competencies, more targeted information, voluntariness with consideration of individual needs and clarification of expectations.